Designing an Authentic Reading Text Module as the Foundation of Students' Background of Knowledge - Fabianto, Eko; Muanifah, Hidayatul (LPPM Universitas Pancasakti Tegal, 2023)
This is a research and development (R & D) study in nature. In conducting this research, the researcher focus on using English for Specific Purposes (ESP) in providing the materials. Some activities involved some experts in certain fields, namely English materials expert and each of study program experts. The objectives of this research are: (1) To produce authentic reading text module for students with heterogeneous backgrounds in knowledge and fields of study. 2. To validate authentic reading text module for students with heterogeneous backgrounds in knowledge and fields of study. Based on the findings on the needs, the reading text module covers relevant and authentic materials which enable to enhance the comprehension of the students. It is believed that the module helps the students as the foundation of their background of knowledge. From the result, the average normalized gain shows up 0, 44 meaning that the design for reading module has an average effectiveness and can describe the students’ background of knowledge. At last, this reference will be able to help in designing a reading text module for each study program at IBN Tegal.